Anniversary meeting: 30 November 1995 - -, - (Proceedings of the Society of Antiquaries of Scotland, 1996)
At the Anniversary meeting the Annual Report was delivered covering topics such as Membership, Meetings, Research and publications. The Treasurer also presented the report on the Society’s finances and the President delivered the President’s Address. The Council for the following session was then elected, as were new applicants for Fellowship. A list of Fellows who died during 1994-1994 was presented. Instructions for Contributors are appended.